Differential effects of left DLPFC anodal and cathodal tDCS interventions on the brain in children with autism: A randomized controlled trial - Jiannan Kang; Juanmei Wu; Xinping Huang; Wenqin Mao; Xiaoli Li (IBRO Neuroscience Reports)
Background: Autism spectrum disorder (ASD) is a complex and heterogeneous neurodevelopmental disorder with few effective treatment options. In recent years, transcranial direct current stimulation (tDCS) has been applied in interventions for ASD, often targeting the left dorsolateral prefrontal cortex (DLPFC). However, studies investigating anodal and cathodal tDCS interventions have reported differing outcomes. Therefore, this study aimed to compare and analyze the effects of these two stimulations through a randomized controlled trial, utilizing both behavioral assessments and EEG proxy markers capable of characterizing the brain's excitatory-inhibitory balance. Methods: This study recruited a total of 24 children with ASD (20 males and 4 females; mean age ± SD: 5.5 ± 1.2 years), who were randomly divided into two groups receiving either anodal or cathodal tDCS targeting the DLPFC. The stimulation intensity was set at 1 mA, administered five times per week for a total of 20 sessions. Behavioral intervention outcomes were assessed using the Social Responsiveness Scale (SRS) and the Autism Behavior Checklist (ABC). Additionally, the study evaluated the effects of tDCS on the brain's excitatory-inhibitory balance by analyzing corrected periodic alpha oscillation power and bandwidth, as well as non-periodic exponent and offset derived from EEG data. Results: Following anodal tDCS intervention, results from the SRS scale indicated a decrease in overall scores, with significant differences observed in social communication and social motivation among children. On the ABC scale, overall scores also decreased, with significant differences noted in sensory behavior, social relating, body and object use, and language and communication skills. Non-periodic exponent and offsets increased following anodal tDCS stimulation, whereas they decreased after cathodal tDCS stimulation. Regarding alpha oscillation power, there was a significant increase following anodal tDCS and a significant decrease following cathodal tDCS. In terms of alpha oscillation bandwidth, there was a reduction following anodal tDCS and an increase following cathodal tDCS. Further correlation analysis revealed that in children who received anodal tDCS intervention, non-periodic exponent showed correlations with behaviors such as social communication. Conclusion: Our study results demonstrated that anodal and cathodal tDCS targeting the left DLPFC had distinct effects on the behavior and excitatory-inhibitory balance of children with ASD. Anodal tDCS intervention appeared to have a more positive impact compared to cathodal intervention. However, the sample size was small, and we focused solely on the effects of tDCS, with our experimental design perhaps not being able to generalize to all external manipulations of excitability in our study. In future research, we will continue to improve the experiments to address these limitations.